2016
DOI: 10.1186/s12876-016-0538-9
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of early stage colorectal cancer patients in Morocco

Abstract: Background: A multicentre cohort study was held in Morocco, designed to evaluate the quality of life of cancer patients. The aim of this paper is to report the assessment of the quality of life of early colorectal cancer patients, before and after cancer treatment, to identify other factors which are related to this quality of life. Methods: We used the third version of the QLQ-C30 questionnaire of the European organization for Research and treatment of Cancer (EORTC) after a transcultural validation. The Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 16 publications
4
19
1
1
Order By: Relevance
“…Similar results were found in other studies with longitudinal QOL measurements [27][28][29] and confirmed by a systematic review of 23 studies regarding the changes in physical-and role functioning after colorectal cancer treatment [30]. Also, worse postoperative physical functioning in older patients compared to younger patients was described previously [7,[32][33][34][35][36][37]. Our results may add that older patients still report poor physical-, social-, and role functioning up to one year after diagnosis compared to their pretreatment level and compared to the reference population, indicating slow recovery or permanently affected functioning.…”
Section: Discussionsupporting
confidence: 88%
“…Similar results were found in other studies with longitudinal QOL measurements [27][28][29] and confirmed by a systematic review of 23 studies regarding the changes in physical-and role functioning after colorectal cancer treatment [30]. Also, worse postoperative physical functioning in older patients compared to younger patients was described previously [7,[32][33][34][35][36][37]. Our results may add that older patients still report poor physical-, social-, and role functioning up to one year after diagnosis compared to their pretreatment level and compared to the reference population, indicating slow recovery or permanently affected functioning.…”
Section: Discussionsupporting
confidence: 88%
“…This is in keeping with previous studies that found rectal cancer patients tend to report more symptoms than when compared to all comers of colorectal cancers. 23 Furthermore, it is also possible that this is a reflection of the timing of the quality of life assessment in our patient cohort. A significant proportion of patients were recruited and assessed during the early post-operative and/or during an acute non-elective hospital admission, where higher levels of symptoms are to be expected.…”
Section: Quality Of Lifementioning
confidence: 99%
“…Artinnya, semakin rendah stadium pada pasien kanker maka semakin tinggi kualitas hidupnya. Hasil penelitian ini didukung oleh penelitian yang dilakukan oleh Mrabti et al (2016) menyatakan bahwa semakin rendah stadium atau stage kanker yang diderita oleh pasien kanker maka semakin baik kualitas hidupnya, hal ini ditunjukkan bahwa pasien dapat berfungsi lebih baik seperti fungsi fisik, peran, emosional, kognitif, dan sosial dibandingkan dengan pasien yang berada pada stadium yang tinggi.…”
Section: Teknik Analisis Dataunclassified